PENGENDALIAN MUTU STRUKTUR PADA PROYEK RUMAH SUSUN STASIUN PONDOK CINA - Betty Rosyana Manurung; Sidiq Wacono (Politeknik Negeri Jakarta, 2020)
Each project can run well and achieve results as planned is expected undoubtedly. Therefore, it requires project quality control. The quality control system in construction projects is essential must be carried out to produce one-time work of a quality that meets the specified standards. This study aims to determine the quality control system for superstructure work and to determine whether the quality of reinforced concrete is according to the requirements. The data used is secondary data, namely, data directly obtained from the project. The data used are tthe concrete compressed test result and reinforcing steel tests held in the laboratory and reinforced concrete data. The analysis results showed that the compress strength of concrete for FC 30 and FC 40 with a test age of 28 days was by the specified requirements, the reinforcement tests S10, S13, S16, S19, S22, S25 meet requirements. For the final result, reinforced concrete found a few defects, but the contractor immediately took corrective action. The analysis shows the implementation of an appropriate quality control process in this project. Keywords : Quality, Control, Concrete, Reinforcement, Construction.